Results from the PolarquEEEst missions. (June 2020) - Abbrescia, M.; Avanzini, C.; Balbi, G.; Baldini, L.; Baldini Ferroli, R.; Batignani, G.; Battaglieri, M.; Boi, S.; Cavazza, D.; Bossini, E.; Carnesecchi, F.; Cicalò, C.; et al.
Abstract: The PolarquEEEst scientific programme consists in a series of measurements of the cosmic ray flux up to the highest latitudes. It started in Summer 2018, when three telescopes made out of scintillators readout by SiPMs were built and installed in Italy, Norway and on a sailboat leaving from North Island, to circumnavigate the Svalbard archipelago and land in Tromsø. They collected data on a latitude range from 44° N up to 82° N, with a dense sampling of the Northernmost interval. The PolarquEEEst mission continued afterwards with a series of measurements in Italy, Southward reaching Lampedusa, and in Germany. In May 2019 the PolarquEEEst collaboration accomplished another important result, installing a cosmic ray observatory for the detection of secondary cosmic muons at Ny Alesund, at 79° N, made of three independent identical detectors positioned a few hundred meters from each other, and synchronized in order to operate together as a network. The configuration used will allow high precision measurements never performed before at these latitudes on a long term, also interesting for their connection with environmental phenomena. The network will also complement the existing stations for the detection of cosmic neutrons at the Svalbard archipelago, enlarging by far the physics scope that is possible to pursue in this field at this peculiar location. Here the various missions are presented, and some preliminary results from the measurements performed are shown.